Leadership in Pesantren: Educational Management Approaches for Spiritual and Academic Development - Musaddad, Ahmad (AKSI: Jurnal Manajemen Pendidikan Islam, 2024)
Pesantren, as an integral part of the Indonesian education system, have adapted to the demands of the times while maintaining a deep approach to religious education. This research focuses on Salafiyah Syafi'iyah Sukorejo Pesantren, analyzing how this pesantren integrates spiritual and academic education in the face of modern social and educational dynamics. This study employs a qualitative approach, involving in-depth interviews, observations, and document analysis to explore aspects of leadership and educational management in the pesantren. The leadership of the kyai in Salafiyah Syafi'iyah Sukorejo Pesantren plays a central role in decision-making, combining spiritual and managerial authority. This pesantren has successfully implemented a unique educational management approach, blending traditional and modern methods. This includes the use of a structured management system for daily operations and a flexible approach to religious education. The pesantren also creates a balance between religious and general education, preparing students to actively contribute to modern society.